Infection and re-infection: stability of complex air transport network - Zou, Mengbang; Guo, Weisi (IEEE, 2021)
Global epidemic propagation rate and structure are strongly coupled with the international air transport network. Due to the network structure, countries are desynchronized in the way infections arise, transported, mitigated, and re-infect again. A global lockdown is detrimental to the international economy, and many argue that unless the whole world is evenly vaccinated, we cannot return to pre-COVID lives. The current challenge is that new waves of re-infection are spreading, and vaccination will take many months to materialise across the world. Here, we show how certain small airports (0.1% of global) contribute much more to the epidemic spread process, irrespective of the actual spreading mechanics. We use trophic coherence as a metric for network stability in directed graphs (e.g., recurring network source of reinfection). We find that the air transport network has a trophic coherence similar to a random expectation (99% of airports form a tightly looped network) and practically all networks need to be equally protected to ensure global security.
Keywords: air transport network; network science; data analysis; epidemics; COVID-19